Vivas for the oral and maxillofacial surgery FRCS - Breeze, John (Surgeon); Parmer, Sat; McLeod, Niall M. H. ([Oxford] : Oxford University Press, 2019)
This volume provides candidates with 100 high-quality viva topics and expert guidance to prepare for this difficult exit oral exam. Written and edited by consultant oral and maxillofacial surgeons who have succeeded in the exam, the text provides comprehensive coverage of theory and practice. Split into 15 chapters of key sub-specialties, all 100 questions are mapped to the surgical curriculum preparing you for the FRCS oral examination.
Also issued in print: 2019.
Includes index.
Specialized.
Description based on online resource; title from home page (viewed on August 7, 2019).
Keywords: Face -- Surgery -- Examinations, questions, etc; Mouth -- Surgery -- Examinations, questions, etc; Maxilla -- Surgery -- Examinations, questions, etc; Oral examinations -- Study guides